Overlapping Guillain-Barré syndrome and Bickerstaff's brainstem encephalitis associated with Epstein Barr virus - Rho, Young Il (Korean J Pediatr, 2014)
A flaccid tetraparesis in Bickerstaff's brainstem encephalitis (BBE) is presumed to be a sign of overlapping Guillain-Barré syndrome (GBS). In addition, BBE and Fisher syndrome, which are clinically similar and are both associated with the presence of the immunoglobulin G anti-GQ1b antibody, represent a specific autoimmune disease with a wide spectrum of symptoms that include ophthalmoplegia and ataxia. A 2-year-old boy presented with rapidly progressive ophthalmoplegia, ataxia, hyporeflexia, weakness of the lower extremities, and, subsequently, disturbance of consciousness. He experienced bronchitis with watery diarrhea and had laboratory evidence of recent infection with Epstein-Barr virus (EBV). He was diagnosed as having overlapping GBS and BBE associated with EBV and received treatment with a combination of immunoglobulin and methylprednisolone, as well as acyclovir, and had recovered completely after 3 months. In addition, he has not experienced any relapse over the past year. We suggest that combinations of symptoms and signs of central lesions (disturbance of consciousness) and peripheral lesions (ophthalmoplegia, facial weakness, limb weakness, and areflexia) are supportive of a diagnosis of overlapping GBS and BBE and can be helpful in achieving an early diagnosis, as well as for the administration of appropriate treatments.